Marginal utility - Simões, N.; Diogo, A. P. (Encyclopedia of quality of life and well-being research, 2020)
The concept of utility is crucial in explaining consumption decisions. Utility can be defined as the satisfaction that a person derives from consumption (Varian 2014). When we consider specifically the impact of an additional unit of a good in satisfaction, we use the concept of marginal utility